MISSION AS RECONCILIATION - A van de Beek (Acta Theologica)
For a long time, missiology operated in the paradigm of civilisation and good citizenship. Since the end of the 19th century, inculturation and social justice have replaced this paradigm. The current focus is on self-affirmation. In his work, Pieter Verster pleads for understanding mission as reconciliation, and this not so much as a variation on social justice, but as a fundamental new relation of God to human beings. Christology is the centre of his missiological paradigm. Renewal of humanity is only possible in the perspective of transcendence: God’s coming in Christ and resurrection to eternal life. In this article, it is argued that it will be a great challenge for scholarly missiology and for the churches to accept this new paradigm, which involves a reconsideration of the basic paradigm of Christianity.